Jurisprudential Analysis of Intention in Realization of Complicity to Crime with an Approach Based on Imam Khomeini’s Views - Mohammad Nozari Ferdowsieh; Majid Nazarian Lenji; Abdullah Omidfard (پژوهش‌نامه متین)
Various evidences in Islamic law attest to the necessity of intention in aiding and abetting a criminal act considering it as an essential element in committing a crime without which it will be difficult to attribute criminal liability to a person and entitle punishment accordingly. This necessity in realization of abetting a criminal act is a source of disagreement among jurisprudents with Imam Khomeini being one of its opponents.  Whereas vastness of executive works in some actions requires involvement of some other factors for realization of perpetrator’s intension, it is necessary to delve into the issue. This is because the abettor under the influence of the perpetrator’s deceit, or to avert threat, or with an intention of doing good may take action to be accused of committing crime in spite of the absence of an intention but due to entitlement as abetting a criminal act. Findings of this paper, developed through a descriptive-analytical method and library documentation, indicate that the rule on existence of an intention for committing a crime is preferable. A review of Imam Khomeini’s Viewpoints, despite sufficiency of evidence and emphasis on the role of common law in determining complicity in crime, shows his tendency to accept such preference. Therefore, in some cases where intention is absent, the title of complicity in crime and entitlement of punishment may be removed.